1997
DOI: 10.1016/s0885-3924(96)00206-0
|View full text |Cite
|
Sign up to set email alerts
|

The edmonton functional assessment tool: Preliminary development and evaluation for use in palliative care

Abstract: The purpose of this article is to report the development and psychometric testing of the Edmonton Functional Assessment Tool (EFAT). The EFAT was developed as a functional outcome measure for use with a palliative care population. The assessment identified ten functional activities important to patients even in the terminal stage of their illness. In addition, a global performance status rating (PS) asked for an overall judgment of functional status after the ten EFAT functions were evaluated. Tests for interr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 13 publications
1
33
0
1
Order By: Relevance
“…Laakso et al 32 used an adapted version of the Functional Independence Measure (FIM); however, published validation studies are warranted. Kaasa et al 38 found that traditional functional tools, such as the Barthel Index and the FIM, were not sensitive enough to detect changes in poorly functioning palliative patients and therefore devised the Edmonton Functional Assessment Tool for physiotherapists and occupational therapists. It correlates with KPS (r = 0.79) and ECOG (r = 0.85), and detects change over time.…”
Section: Outcome Measurementioning
confidence: 99%
See 1 more Smart Citation
“…Laakso et al 32 used an adapted version of the Functional Independence Measure (FIM); however, published validation studies are warranted. Kaasa et al 38 found that traditional functional tools, such as the Barthel Index and the FIM, were not sensitive enough to detect changes in poorly functioning palliative patients and therefore devised the Edmonton Functional Assessment Tool for physiotherapists and occupational therapists. It correlates with KPS (r = 0.79) and ECOG (r = 0.85), and detects change over time.…”
Section: Outcome Measurementioning
confidence: 99%
“…It correlates with KPS (r = 0.79) and ECOG (r = 0.85), and detects change over time. 38 The second version of the Edmonton Functional Assessment Tool (EFAT-2) 39 measures 10 domains that may affect function: communication, pain, mental status, dyspnea, balance, mobility, locomotion, daily activities, fatigue, and motivation (See Appendix). Scoring is from 0 to 30, low scores indicating higher function and vice versa.…”
Section: Outcome Measurementioning
confidence: 99%
“…The most common method of assessment was circumferential measurements (78%), followed by skin descriptors (73%) and function (72%) using EFAT-2 (Kaasa and Wessel 2001). See Figure 1.…”
Section: Assessment and Goalsmentioning
confidence: 99%
“…The EFAT is a validated tool that allows a physiotherapist or trained nurse to determine the functional performance of patients with advanced cancer, as well as the evaluation of factors that contribute to the functional impairment, such as communication, mental status, pain, and dyspnea, among others. 36,37 The functional status of advanced cancer patients can be assessed in the research setting using the FIM. 38,39 The FIM includes 18 items covering independence in self-care, sphincter control, mobility, locomotion, communication, and social cognition.…”
Section: Instruments For Assessment Of Function and Prognosismentioning
confidence: 99%